Biosorption of Methyl Orange from Aqueous Solutions by Silk Maize as an Eco-friendly Biosorbent - Rashidi Ghane, Elham; Momenheravi, Mohammad; Borjali, Sara; Ardalan, Touran; Ardalan, Pouran (Asian Journal of Chemistry, 2011)
In this study, silk maize activated carbon developed from maize waste material was tested as biosorbent for the removal of methyl orange dye from aqueous solutions. Adsorption of methyl orange onto this low-cost natural adsorbent was studied by batch adsorption at different temperature. The effects of contact time, adsorption dose and initial dye concentration on adsorption capacity were studied. The kinetic of the sorption was analyzed using the pseudofirst- order, pseudo-second-order and Elovich kinetic models. The data showed that the secondorder equation was the more appropriate. The equilibrium sorption isotherms have been analyzed by the Langmuir, Freundlich, Tempkin and Harkins-Jura (H-J) models. The Langmuir isotherm has the highest correlation coefficient (R2 > 0.99). The apparent thermodynamic parameters were calculated and the obtained values support the conclusion that the reactive dye molecules sorbs by exothermic process.